ANALISIS KESULITAN SISWA SMK DALAM MENYELESAIKAN SOAL MATERI TRIGONOMETRI - Vina Novianti; Marchasan Lexbin Elvi Judah Riajanto (IKIP Siliwangi, 2021)
This study was conducted aiming to describe the types of difficulties experienced by vocational students when working on trigonometry problems. This type of research is conducted using descriptive qualitative with a description test instrument total 4 questions. The data analysis technique uses the calculation of the level of control and the percentage of student difficulties. The subjects of this study were 31 students of class XI SMK PGRI 1 Cimahi. Based on the research that has been done, it can be concluded that the difficulties experienced by vocational students when completing trigonometric problems in the school are 1) Difficulty understanding the problem that is 100%, 2) Difficulty not continuing the completion process that is 54.1%, 3) Difficulty completing questions / the calculation is 40.8% and 5) the difficulty of not writing results is 80.8%. The causes of difficulties experienced by students are 1) Students are not accustomed to understanding the problem that is not writing out what is known and asked in solving problems, 2) Students are not accustomed to writing the final results of the questions that have been done even though the results found were correct, and 4) Lack of student understanding and concept understanding of the material. So that learning needs to prioritize concepts and understanding of material that has been learned beforehand.